Analisis Implementasi Penyusunan Laporan Keuangan Pada Usaha Mikro Kecil Dan Menengah (Umkm) Ramp Kelapa Sawit Fjb Group Berdasarkan (Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah (Sak Emkm) - Prita Susan Oktaviani; Viras Alti Pidola (CV. Kalimasada Group, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of Indonesia's economy, playing a key role in job creation and contributing significantly to the Gross Domestic Product (GDP). However, despite their great potential, most MSMEs still face challenges in financial management, particularly in preparing financial reports that comply with applicable standards. Many MSME actors rely only on simple record-keeping without referring to established accounting standards.To address this issue, the Financial Accounting Standards Board (DSAK) and the Indonesian Institute of Accountants (IAI) issued the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in 2018. SAK EMKM is designed to enable MSMEs to prepare financial reports that are simple, yet informative and compliant with standards. This study aims to analyze the implementation of financial reporting at the FJB Group Palm Oil Ramp MSME located in Block E, Seresam Village, Seberida District, Indragiri Hulu Regency, based on the SAK EMKM. The study uses a descriptive qualitative method through observation, interviews, and documentation techniques. The results show that the FJB Group MSME has not yet applied financial reporting in accordance with SAK EMKM standards. The financial records are still maintained manually and limited to daily income and expenditure, without preparing a proper balance sheet or income statement. The main obstacles in implementing this standard are limited accounting knowledge and a lack of competent human resources in the field of finance.This study recommends SAK EMKM-based accounting training and support from the government and other stakeholders to improve financial literacy among MSME actors. The adoption of these accounting standards is expected to improve the accuracy of financial reports and support better business decision-making.